Pengaruh Kinerja Guru Terhadap Kepuasan Santri Studi Komparatif Pada Gontor Kampus 7 dan Pesantren Ushuluddin Kalianda - Saifullah Saifullah; Subandi Subandi; Nanang Supriadi (LP2M Universitas Islam Ahmad Dahlan, 2026)
This study aims to analyze and compare the influence of teacher performance on student (santri) satisfaction at Pondok Modern Darussalam Gontor Campus 7 (a pure modern Islamic boarding school) and Pondok Pesantren Ushuluddin Kalianda (a combinative Islamic boarding school). An explanatory quantitative approach with a cross-sectional design was employed. From a population of 1,159 active students in the 2025–2026 academic year, a sample of 92 respondents was selected using proportional random sampling based on the Slovin formula (10% error tolerance). Data were collected through closed-ended Likert-scale questionnaires and analyzed using simple linear regression and Fisher's Z comparative test.The results showed that: (1) Teacher performance had a positive and significant influence on student satisfaction at Gontor Campus 7, contributing (R2) 35.9%; (2) Teacher performance had a positive and significant influence on student satisfaction at PP Ushuluddin Kalianda, contributing (R2) 57.0%; (3) The Fisher's Z test yielded a Zvalue of 1.361 (lower than the Ztabel of 1.96), indicating no statistically significant difference in the influence of teacher performance on student satisfaction between the two institutions. Although PP Ushuluddin descriptively showed slightly higher and more homogeneous mean scores, teacher performance essentially proved to be a crucial pillar in enhancing student satisfaction across both types of Islamic boarding schools.